Variation in the bromatological properties of three types of pastures for livestock use in the Barbas Bremen soils conservation district (Revista de Investigaciones Universidad del Quindío, 2017)
The Municipality of Filandia is located on the western slope of the Central Cordillera of Colombia, Alto Cauca basin. Its territory represents 5.58% of the total extension of the Department of Quindío. This municipality has an increased livestock activity with dual purpose (milk and meat) as the most important economic activity for the sustenance of families. We studied the agricultural practices of the members of the livestock association of the municipality and we also performed a bromatological analysis of pastures and lands, in order to know their quality as part of the department's integrative strategy that promotes the least harmful techniques of livestock activity for the environment. We found that the nutritional values of the pastures have medium protein levels and low fat values in relation to the minimum reference frames. This can be attributed to the high rainfall periods witnessed in the region and to the non-standardized and controlled livestock processes, since in such farms there is no rotation, this being the cause of maximum use of the paddock per unit of livestock.
Keywords: Soils; bromatological analysis; cattle